2004
DOI: 10.1177/1076167503252922
|View full text |Cite
|
Sign up to set email alerts
|

Cancer CAM™: Web-Based Continuing Education for Health Professionals

Abstract: Nurses and health educators who work with cancer patients are often asked about complementary and alternative medicine (CAM) therapies. "CAM and the Prostate Cancer Patient" is the prototype module for an online continuing education series on CAM. More than 60 nurses and health educators tested the product online. Outcome data indicate that such a program can increase learners' CAM knowledge and perceived self-efficacy in addressing patient questions about CAM. Qualitative responses from testers indicate an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…For example, a prototype module ('CAM and the Prostate Cancer Patient') has been developed for a webbased program for nurses and healthcare professionals working with cancer patients. [29] Initial evaluations of this prototype found that the module increased nurses and health educators' knowledge and self-efficacy in CAM and in answering patient's queries. In order to maintain pace with the burgeoning popularity of CAM with the general public, it is important that an appropriate medium through which to convey the learning message is chosen so as to maximise quickly the success of any resource.…”
Section: Cam Therapies and Associations Between CC Nurses Use Knowlementioning
confidence: 99%
“…For example, a prototype module ('CAM and the Prostate Cancer Patient') has been developed for a webbased program for nurses and healthcare professionals working with cancer patients. [29] Initial evaluations of this prototype found that the module increased nurses and health educators' knowledge and self-efficacy in CAM and in answering patient's queries. In order to maintain pace with the burgeoning popularity of CAM with the general public, it is important that an appropriate medium through which to convey the learning message is chosen so as to maximise quickly the success of any resource.…”
Section: Cam Therapies and Associations Between CC Nurses Use Knowlementioning
confidence: 99%